Analyzing the Customers Attitude Toward Banking Services Introduced By Libyan Commercial Banks From Islamic View: Applied Study in some Libyan Commercial Banks in Benghazi - عبد الجواد إدريس الحبو ني د. إدريس (Scientific Journal of University of Benghazi, 2026)
This research aims to analyze the Customers Attitude Toward Banking Services Introduced by Libyan commercial Banks in Benghazi from Islamic View, by being aware of the extent of applying Islamic marketing services in Libyan banking. This research conducted from personnel customers view, the research results has revealed that the banking services of Libyan banks is not in conformity with Islamic banking services, and accordingly some recommendations have been suggested, such as developing the banking services which is submitted by Libyan banks in order to establish Islamic banking services system within the Libyan banking system and spreading the Islamic banking culture and Islamic transactions in banking services. Another study may be conducted to identify other customers attitude towards Islamic banking services.